Effect of pH, temperature and chloride concentrations on the corrosion behaviour of welded 316L stainless steel - Ramlee, Norlaila (2008)
The aim of this work is to determine the effect of pH, temperature and chloride concentrations on the corrosion behavior of welded 316L stainless steel. An electrochemical, immersion and salt spray tests were employed. Corrosion behavior of welded 316L stainless steel in acidic and alkaline solutions at different concentrations and temperatures was investigated. The results showed that the weld metal (WM) zone was the most critical zone for pitting corrosion in alkaline (pH=7.64) and acidic (pH=I.83) conditions at temperature of 50Â°C. The results correlated well to the microstructural features of the metal studied. While, in the immersion test the results indicated that the highest corrosion rate was observed in stainless steel sample tested in 10% FeCh at 50Â°C for both 72 and 144 hours (40.6453 mm/yr and 40.8592 mm/yr). It was also found that the salt spray test had no considerable effect on the weldment of 316L SS probably due to the limited time of testing. Field Emission Scanning Electron Microscopy (FESEM) and Optical Microscopy (OM) were used to examine the microstructure features of the tested samples in order to determine the extent of corrosion attack and type of corrosion.